Desain Pembelajaran Pendidikan Agama Islam (PAI) Melalui Aplikasi Tik-Tok - Fandi Asy’arie, Bima; Noto Suseno, Nugroho (LP3M STAI Ibnurusyd, 2024)
One very important component in the formation of generations is how a teacher can design the learning process of Islamic religious education (PAI) optimally, and of course students are able to feel an innovation implemented by teachers in their learning process. The objectives of this study are (1) Determine the steps in designing PAI learning with supporting applications, (2) Find the benefits of the tik-tok application as a learning medium. The type used in this study is using a qualitative approach with a literature method (library research). The results in this study are to determine the steps, namely (1) Determining the structure of the material, (2) Determining the design specifications to be developed, (3) Making steps in making learning designs on available media, (4) Making elements of learning models. Then, the benefits and impact of the tik-tok application as a learning medium PAI (1) as a fun learning medium, (2) as a more active student. make schoolwork more memorable. Furthermore, supporting applications used to design PAI learning include “Benime, Text Voice Free, Picsart, Kine Master, Video ke MP3 Converter dan Google Drive”. Thus, after the learning design is made then uploaded through the Tik-Tok application as the main media.